2022
DOI: 10.4049/jimmunol.208.supp.53.23
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Induction of TH1-like Tregs Controls Anti-viral Responses

Abstract: Regulatory T cells (Tregs) are an immunosuppressive cell population that inhibits immune cell function to maintain peripheral tolerance and homeostasis. We have previously shown that Treg-- response to interferon gamma (IFNγ) is required for response to cancer immunotherapy. We aimed to broaden these findings and determine the impact of Treg response to IFNγ and the IFNγ-inducing cytokine IL12, during viral infection. Mice with Treg-restricted deletion of the IFNγ receptor (IFNGR1, Ifngr1L/LFoxp3Cre-YFP) or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, cells within cluster 13 highly expressed genes associated with T helper cell type 1 (T H 1) phenotype, including TBX21 (gene encoding T-bet), CCL4 , CCL5 , and IFNG (gene encoding IFN-γ), suggesting a specialized function of T regs for T H 1-related and antiviral immune responses (fig. S4D) ( 27 29 ). We also detected augmented expression of CD39 and CD27 in T reg clusters 9 to 12 (TNFR + T regs ), which highlighted different programs regulating activated T reg function in the TME.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cells within cluster 13 highly expressed genes associated with T helper cell type 1 (T H 1) phenotype, including TBX21 (gene encoding T-bet), CCL4 , CCL5 , and IFNG (gene encoding IFN-γ), suggesting a specialized function of T regs for T H 1-related and antiviral immune responses (fig. S4D) ( 27 29 ). We also detected augmented expression of CD39 and CD27 in T reg clusters 9 to 12 (TNFR + T regs ), which highlighted different programs regulating activated T reg function in the TME.…”
Section: Resultsmentioning
confidence: 99%
“…T regs are important regulators of immune homeostasis and tissue repair but suppress antitumor immunity (1,3,10,29,(55)(56)(57)(58). A previous study revealed conserved effector T reg phenotypes that are shared between normal tissues and melanoma (45).…”
Section: Discussionmentioning
confidence: 99%